2015
DOI: 10.1039/c5ra13866c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically structured catalyst layer for the oxygen reduction reaction fabricated by electrodeposition of platinum on carbon nanotube coated carbon fiber

Abstract: Cost-efficient fabrication of cathode catalyst layer having low Pt-loading and high oxygen reduction reaction (ORR) performance is of prime importance towards commercialization of low temperature fuel cells. Here, an attempt has been made to fabricate hierarchically structured and cathode catalyst layer consisting of Pt-nanoparticle clusters supported on defective carbon nanotube (CNT) coated carbon fiber (CNTCF). CNTs are grown on carbon fiber (CF) by chemical vapor deposition (CVD), while electrodeposition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The four-electron pathway for Pt-based catalysts prepared by electrodeposition method has been reported earlier. 37,43,46 Figure 6 displays a comparison of the ORR polarization curves of Pt/MWCNT-A (Figure 6a) and Pt/MWCNT-B (Figure 6b) with commercial Pt/C measured at 1900 rpm. The values of half-wave potential (E 1/2 ) calculated from the RDE data are given in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The four-electron pathway for Pt-based catalysts prepared by electrodeposition method has been reported earlier. 37,43,46 Figure 6 displays a comparison of the ORR polarization curves of Pt/MWCNT-A (Figure 6a) and Pt/MWCNT-B (Figure 6b) with commercial Pt/C measured at 1900 rpm. The values of half-wave potential (E 1/2 ) calculated from the RDE data are given in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of similar clusters at certain active sites on the surface of CNTs has been reported earlier. 43,44,49 Sharma and Kar suggested that the corroded rough surface of the CNTs after acid-treatment may provide active sites for nucleation. 43 Huang et al suggested that the number of Pt nuclei formed on the carbon surface depends on the hydrophilicity and uniformity of the support material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations